(3CeGdj GdeMGedjs - (3GdeMGedj, GdVHj, CHh YHO Gddg, GdMSjf Hf ESeGYjd Hf eMeO Hf ESeGYjd, J (B330(3g`s ((3eMeO Hf YHO GdbGOQ GdMfajs)
(3ChdgG (B:s
(3CNHQfG CHh GdZfGje eMeO Hf Ydj Hf GdMSf (B... (3bGd(B: (3Ef eYGhjI cJH Edi eQhGf(B: (3EPG SQb GdQLd agh CMb HSQbJg MjK hLOgG(B...s
(3BNQgG (B:s
(3MOKfG YHO Gddg Hf THjH, MOKfj CjhH Hf SdeGf, MOKfj CHh HcQ Hf CHj ChjS(B... (3Yf CfS Cf QShd Gddg Udi Gddg Ydjg hSde LYd YJbgG UOGbgG(B. (3BNQ GdLRA GdChds
(3QhGjI(B: (3CHj eMeO YHO Gddg Hf YHjO Gddg Hf jMji Hf RcQjGs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe(B: (3L(B2(3, U(B234s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3GdMOjK hGdeUWdMs